ChemInform Abstract: Synthesis of Extended Chromophores Derived from 5, 5‐Dimethyloxyluciferin by Barton—Kellogg Methodology. Issue 41 (7th October 2014) - Wuerfel, Hendryk; Monteiro Leite Ciscato, Luiz F.; Weiss, Dieter; Goerls, Helmar; Beckert, Rainer
Abstract the UV/vis absorption and fluorescence properties in tetrahydrofuran are also investigated